Estudio de Factibilidad para la creación de una comercializadora y distribuidora de productos derivados de la guadua. (2013)
Currently the bamboo sector is promising in the EjeCafetero´s economy, despiteof being a typical product of this region, which is a strength and resource at the same time ofan alternative that could improve the socioeconomic conditions of the environment. The sector comes while asserting the importance of the resource of bamboo for the environment and the economy, through a portfolio of products in which the relationship between idiosyncrasy and innovation resulting in the need to support their growth and consolidation within the regional productive apparatus. However, this sector requires further strengthening of business that may arise from the academy, for which one of its objectives and goals is to support the socioeconomic growth of the Department of Quindío. This investigation aims to make inroads into the value chain of guadua, more specifically at the end of this, proposing to reach consumers with producers, by means of two business lines represented on floors laminated construction and decoration items, such as furniture and handicrafts for the tourism sector. Different studies suggest the feasibility and viability of these products on the market, as well as the needs of consumers and their characteristics will be show in the following investigation.